The use of genetic risk prediction to study prodromal Alzheimer's disease in the PISA study: Genetics/genetic factors of Alzheimer's disease. (7th December 2020) - Lupton, Michelle K.; Fazlollahi, Amir; Ceslis, Amelia; Fripp, Jurgen; Rose, Stephen; Salvado, Olivier; Robinson, Gail; Guo, Christine; Breakspear, Michael; Martin, Nick
Abstract: Background: Neuropathology accumulates for decades prior to the onset of cognitive decline in Alzheimer's disease (AD). Interventions to modify the course of the disease have the greatest potential to avert neuronal death and later disease burden if they are introduced during this crucial window. Our prospective cohort study, "Prospective Imaging Study of Ageing: Genes, Brain and Behaviour" (PISA) aims to characterise the natural history of AD at its prodromal phase. Using genetic risk prediction we have identified middle‐aged and older Australians at high risk of dementia to enable the discovery of biological markers of early neuropathology, identify modifiable risk factors, and establish the very earliest phenotypic and neuronal signs of disease conversion. Method: We utilized APOE genotype and polygenic risk scores (PRS) to identify individuals at high and low risk of AD. We have leveraged our extensive in‐house cohorts, comprising ∼15, 000 individuals aged 40‐70 years with available genome wide genotyping data to generate a genetically enriched cohort for investigating prodromal markers for AD. Online surveys and cognitive testing are used to collect information from a national sample currently totally nearly 3, 000 participants. Subjects (N = 400) from a defined at‐risk cohort and positive controls (clinical cohort of patients with mild cognitive impairment and/or early AD) have taken part in onsite visits for lifestyle monitoring, cognitive testing, blood sample donation, MRI and PET imaging. Result: A high prediction accuracy for AD with an AUC of 78.2% can be achieved by a prediction model including APOE genotype, and PRS (containing GWAS association SNPs with P value <0.5) with the PRS adding significant predictive value over APOE alone. The association of genetic factors with baseline imaging and neuropsychological phenotypes will be presented as well as multivariate analysis investigating the influence of genetic risk on inter‐individual phenotypic relationships. Conclusion: The PISA study is an at risk AD cohort enriched by genome‐wide risk prediction, aiming to validate early markers of prodromal Alzheimer's disease that can be utilized in middle age. This study will help elucidate changes in early prodromal AD risk variants observed in middle age, and evaluate which measures show the earliest changes.